2013
DOI: 10.1016/j.cell.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in IRF4 Affects Human Pigmentation through a Tyrosinase-Dependent MITF/TFAP2A Pathway

Abstract: Sequence polymorphisms linked to human diseases and phenotypes in genome-wide association studies often affect non-coding regions. A single nucleotide polymorphism (SNP) within an intron of the gene encoding Interferon Regulatory Factor 4 (IRF4), a transcription factor with no known role in melanocyte biology, is strongly associated with sensitivity of skin to sun exposure, freckles, blue eyes and brown hair color. Here we demonstrate that this SNP lies within an enhancer of IRF4 transcription in melanocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
192
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(215 citation statements)
references
References 67 publications
(79 reference statements)
9
192
2
5
Order By: Relevance
“…18,65,66 Our data do not establish whether these genetic findings directly contribute to IRF4 expression in PTCLs. For example, IRF4 CNAs in IRF4-positive PTCLs might relate to increased polysomy rather than focal IRF4 gains.…”
Section: Discussioncontrasting
confidence: 59%
“…18,65,66 Our data do not establish whether these genetic findings directly contribute to IRF4 expression in PTCLs. For example, IRF4 CNAs in IRF4-positive PTCLs might relate to increased polysomy rather than focal IRF4 gains.…”
Section: Discussioncontrasting
confidence: 59%
“…This rs12203592 * T polymorphism was found to be strongly associated with darker hair colour, hair greying, lighter eye colour and reduced skin tanning response to sunlight [19,73,75] and it lies within an enhancer element that drives IRF4 transcription in melanocytes. The rs12203592 * T allele impairs binding of the TFAP2A transcription factor that, together with the melanocyte master regulator MITF, regulates the activity of the enhancer [76] . It has also been found that MITF directly or indirectly regulates IRF4 expression, and that TYR expression depends on IRF4 protein [76] .…”
Section: Irf4: a Gene For Tanning And Naevimentioning
confidence: 99%
“…The rs12203592 * T allele impairs binding of the TFAP2A transcription factor that, together with the melanocyte master regulator MITF, regulates the activity of the enhancer [76] . It has also been found that MITF directly or indirectly regulates IRF4 expression, and that TYR expression depends on IRF4 protein [76] . Asian and African populations are fixed for the rs12203592 * C allele, being monoallelic, with only European populations possessing the rs12203592 * T at around 17% allele frequency.…”
Section: Irf4: a Gene For Tanning And Naevimentioning
confidence: 99%
“…IRF4 and IRF8 were initially thought to be exclusively expressed in cells of immune lineages. However, recent reports have also identified IRF4 and/orIRF8 expression in melanocytes, adipocytes, smooth muscles, cardiac muscles and neurons where they perform diverse functions (Eguchi et al, 2011; Guo et al, 2014; Jiang et al, 2013; Jiang et al, 2014a; Praetorius et al, 2013; Xiang et al, 2014; Yoshida et al, 2014; Zhang et al, 2014). …”
Section: Introductionmentioning
confidence: 99%